Study of abrasive action on surface roughness and worn mass of laminated composites: production and evaluation - Jovanović, Jelena; Mitrović, Nikola; Gajević, Sandra; Miladinović, Slavica; Blagojević, Jasmina; Skulić, Aleksandar; Stojanović, Blaža (Advanced Technologies and Materials, 2025)
This study examined the effect of abrasive action on the surface roughness and mass loss of laminate composites produced by the wet lay-up method. The paper describes in detail the production process of these composites and after the production process, the surface was analysed using an optical microscope. Surface roughness was monitored in the transverse and longitudinal directions, before and after processing with P3000 grit sandpaper, where a significant increase in roughness was observed with minimal mass loss. A more detailed analysis of mass loss included precise measurements in the time interval from 1 to 5 minutes, with the results showing that with extended grinding time the amount of worn material increases. Additionally, analysis using an optical microscope confirmed the successful production of laminate composites, with very little presence of trapped air bubbles recorded, indicating the high efficiency of the applied production process. Considering the characteristics of the used epoxy resin, the obtained results indicate high wear resistance of laminate composites, which is crucial for achieving aesthetically attractive components.